An Endometrioid Ovary Cyst and Fallopian Tube in the Inguinal Canal: Conservative or Surgical Management? - Sema Ovalı; Ahmet Yılmaz; Gürkan Zorlu (Gynecology Obstetrics & Reproductive Medicine)
The presence of an ovary in the inguinal canal, presenting as an inguinal hernia is an extremely rare condition in premenaposal women. We present a case, which was managed expectantly before but needed surgery thereafter.